2016
DOI: 10.18311/mvpjms/2016/v3/i1/738
|View full text |Cite
|
Sign up to set email alerts
|

Study of Eosinophil Count in Nasal and Blood Smear in Allergic Respiratory Diseases

Abstract: Introduction: Allergic rhinitis and asthma are two very common allergic diseases of respiratory tract in pediatric patients. In this geographical area, where the prevalence of allergens exists, the role of allergens as the etiological factor is higher in allergic respiratory disorders. Confirmation of allergen as etiologic agent is cumbersome in a small setup, where IgE estimation and allergy tests are not accessible. In this study, the simple test of peripheral smear and nasal smear eosinophil count as a reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…Higher eosinophil count was found in patients with allergic rhinitis (4.49%) compared to controls (2.36%). These results were consistent with Sonawane et al [2], Demirjian et al [8] and Brakhas et al [10]. A weakly positive correlation was found between serum log IgE and eosinophil levels in patients with allergic rhinitis which was also evident in study conducted by Brakhas et al [10].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Higher eosinophil count was found in patients with allergic rhinitis (4.49%) compared to controls (2.36%). These results were consistent with Sonawane et al [2], Demirjian et al [8] and Brakhas et al [10]. A weakly positive correlation was found between serum log IgE and eosinophil levels in patients with allergic rhinitis which was also evident in study conducted by Brakhas et al [10].…”
Section: Discussionsupporting
confidence: 91%
“…Estimation of serum IgE and eosinophil levels can serve as a simple, economical and reliable investigative tool in the diagnosis of allergic rhinitis [1,2]. Considering the above background, the aim and objectives of the present study was to determine serum IgE and eosinophil levels in patients with allergic rhinitis and healthy controls, men and women, of different age groups and establish a correlation between serum IgE and eosinophil.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kumar et al [5]: dust and cold weather changes were allergens reported in 81% and 62% respectively. Also, Sonawane et al [23] reported dust in 54 (87.1%), weather changes 37 (59.7%), history of family atopy 27 (43.6%) and animal pets13 (21.0%). Family history of atopy was a strong risk factor in this study like in Mercer et al [16] who reported that family history was positive for AR in 88% of their patients.…”
Section: Discussionmentioning
confidence: 96%
“…4,12 El diagnóstico de la NARES se basa en la presencia de síntomas de la enfermedad con pruebas cutáneas negativas, IgE total normal y presencia de eosinófi los en citología nasal (> 20 %), así como ausencia de respuesta ante pruebas específi cas nasales de provocación o ausencia de IgE específi ca en secreciones nasales. 13,14,15,16 El tratamiento es principalmente con corticoides nasales dado que la eosinofi lia nasal indica buena respuesta a esteroides tópicos. Los corticoides nasales disminuyen los síntomas de la enfermedad y reducen el tamaño y recurrencia de los pólipos nasales.…”
Section: Introductionunclassified